Use of Extracorporeal Membrane Oxygenation in Pneumocystis Pneumonia of an Infant with AIDS - Grégoire Cane; Arnaud De Boislambert; Charlotte Sgro; Pierre Lavedan; Hélène Foulgoc; Nadir Tafer; Alexandre Ouattara (Case Reports in Pediatrics)
Pneumocystis pneumonia is a common complication of cellular immunosuppression and may trigger severe pulmonary complications. Rapid onset of acquired immunodeficiency syndrome is possible in infants infected with human immunodeficiency virus (HIV). We report here the case of a 13-week-old girl who was previously healthy presenting with altered immunity and refractory acute respiratory distress syndrome (ARDS) initially attributed to bacterial pneumonia. Venovenous extracorporeal membrane oxygenation (VV-ECMO) was initiated because her condition was poor. An HIV infection was later fortuitously diagnosed after accidental exposure of a nurse to the child’s urine. The mother had congenitally transmitted HIV to the child after late (undetected) infection during pregnancy. The lung lesions were finally attributed to Pneumocystis pneumonia. We prescribed combined antiretroviral, antibiotic, and steroid therapy aimed at preventing immune reconstitution inflammatory syndrome. VV-ECMO weaning progressed over 30 days to the time of decannulation, rapidly followed by extubation and hospital discharge. The case highlights the fact that rare curable causes of refractory pediatric ARDS should always be investigated early. VV-ECMO should not be excluded as an ARDS treatment for immunocompromised children.